Ankyloglossia affecting breastfeeding: A case series - Jamani, Nurjasmine Aida; Ardini, Yunita Dewi; Harun, Nor Asilah (2019)
Ankyloglossia also known as ‘tongue tie’ is defined as a congenital anomaly caused by an abnormally tight lingual frenulum. Around 5% of newborns are affected and it occurs more common in males. Ankyloglossia can lead to a variety of problems such as breastfeeding problems, speech, oral hygiene and social tongue movements. The tongue-tie’s effect on breastfeeding has been associated with sore nipples,poor infant weight gain, neonatal dehydration and shorter breastfeeding duration.